'Dual‐reference' method for high‐precision infrared measurement of leaf surface temperature under field conditions. Issue 6 (25th September 2021) - Muller, Jonathan D.; Rotenberg, Eyal; Tatarinov, Fyodor; Vishnevetsky, Irina; Dingjan, Tamir; Kribus, Abraham; Yakir, Dan
Summary: Temperature is a key control over biological activities from the cellular to the ecosystem scales. However, direct, high‐precision measurements of surface temperature of small objects, such as leaves, under field conditions with large variations in ambient conditions remain rare. Contact methods, such as thermocouples, are prone to large errors. The use of noncontact remote‐sensing methods, such as thermal infrared measurements, provides an ideal solution, but their accuracy has been low ( c . 2°C) owing to the necessity for corrections for material emissivity and fluctuations in background radiation L bg . A novel 'dual‐reference' method was developed to increase the accuracy of infrared needle‐leaf surface temperature measurements in the field. It accounts for variations in L bg and corrects for the systematic camera offset using two reference plates. We accurately captured surface temperature and leaf‐to‐air temperature differences of needle‐leaves in a forest ecosystem with large diurnal and seasonal temperature fluctuations with an uncertainty of ± 0.23°C and ± 0.28°C, respectively. Routine high‐precision leaf temperature measurements even under harsh field conditions, such as demonstrated here, opens the way for investigating a wide range of leaf‐scale processes and their dynamics.